Prevention of Development of Postoperative Dysesthesia in Transforaminal Percutaneous Endoscopic Lumbar Discectomy for Intracanalicular Lumbar Disc Herniation: Floating Retraction Technique - Cho, J. Y.; Lee, S.-H.; Lee, H.-Y. (min - Minimally Invasive Neurosurgery, 2011)
Transforaminal percutaneous endoscopic lumbar discectomy (PELD) has become a routine surgical procedure because it is minimally invasive. Perioperative complications such as dural injury, infection, nerve root irritation and recurrence can occur not only with PELD, but also with conventional open microsurgery. In contrast, post-operative dysesthesia (POD) due to existing dorsal root ganglion (DRG) injury is a unique complication of PELD. When POD occurs, even if the traversing root has been successfully decompressed, it hinders swift recovery and delays the return to daily routines. Thus, prevention of POD is the key to successful and widespread use of PELD.From January 2006 to December 2008, 154 patients underwent percutaneous endoscopic discectomy by floating retraction technique at 160 disc levels under local anesthesia. This approach towards the superomedial border of the lower pedicle and the cannula can be placed by gentle retraction of the root with perineural fat instead of direct compression of dorsal root ganglion. The clinical outcomes were assessed using the Visual Analogue Scale (VAS, 0–10 point) for radicular pain and low back pain, and using the Oswestry Disability Index (ODI) for functional status. Perioperative complications and recurrence were reviewed.The mean age was 45 years, the mean operative time was 36 min and the mean follow-up period was 3.4 years. The mean hospital stay for endoscopic discectomy was 1.8 days. No patient underwent repeated PELD or convert microsurgery by incomplete removal of the ruptured particle. All patients experienced early relief of symptoms, as determined by VAS and ODI. No patient developed POD. 1 patient experienced dural injury. There was 1 case of discitis. The recurrence rate was 1.95% (3 patients).Transforaminal percutaneous endoscopic lumbar discectomy for intracanalicular lumbar disc herniation is a safe and effective procedure. The floating retraction technique is recommended to avoid development of POD.
Keywords: PELD; dysesthesia; endoscopic discectomy